Getting to market - Wolf, Charles, 1924-; Rand Corporation (Santa Monica, CA : RAND, 1991)
Although an enormous amount of literature has appeared on how to convert capitalist market economies to socialist centrally planned ones, the reverse problem of converting socialist economies into capitalist ones has received scant attention. Such a transformation depends on implementing simultaneously, or at least contemporaneously, a package of six closely linked and mutually supporting elements: (1) monetary reform to ensure control of the money supply and credit; (2) fiscal control to assure budgetary balance and to limit monetization of a budget deficit if one occurs; (3) price and wage deregulation to link prices and wages to costs and productivity, respectively; (4) privatization, legal protection of property rights, and the break-up of state monopolies to provide for competition as well as worker and management incentives that reflect changes in relative market prices; (5) a social "safety net" to protect those who may become unemployed as transformation proceeds; and (6) currency convertibility to link the transforming economy to the world economy and to competition in international markets. The process of transforming command, non-market economies to market ones is both better understood and more tractable than the public debate suggests. The practical problem created by impending transformation is that the reigning leadership is very likely to be among the losers in terms of power, privilege and prestige.
Originally published in: The National Interest, Spring 1991.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Capitalism; Economic development; Mixed economy